Web information systems - Taniar, David; Rahayu, Johanna Wenny (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
The Internet is already more widely deployed than any other computing system in history and continues to grow rapidly. New technologies, including high speed wide area network and improved software support for distribution, promise to make the Internet much more useful for general purpose distributed computing in the future. This book is dedicated to the new era of information systems on web environments, due to not only the growing popularity of the web technology but also the roles that web technology play in modern information systems. The major elements of web information systems include XML technologies, web mining and querying, web-based information systems, information extraction, and web semantics